Megakaryocytes and platelets express nicotinic acetylcholine receptors but nicotine does not affect megakaryopoiesis or platelet function - Schedel, Angelika; Uhlig, Stefanie; Bieback, Karen; Bugert, Peter (Platelets, 2016)
In our previous investigations we have shown that platelets and their precursors express nicotinic α7 acetylcholine receptors (nAChRα7) that are involved in platelet function and in vitro differentiation of the megakaryoblastic cell line MEG-01. In this study, we were interested in the expression analysis of additional nAChR and the effects of nicotine in an ex vivo model using megakaryocytic cells differentiated from cord blood derived CD34+ cells (CBMK) and an in vivo model using blood samples from smokers. CBMK were differentiated with thrombopoietin (TPO) for up to 17 days. Quantitative real-time PCR (QRT-PCR), Western blot analysis and flow cytometry were used to investigate nAChR expression (nAChRα7, nAChRα4, nAChRβ2) and nicotine effects. In blood samples of 15 nonsmokers and 16 smokers platelet parameters (count, mean platelet volume - MPV and platelet distribution width - PDW) were determined as indicators for changes of in vivo megakaryopoiesis. Platelet function was determined by the use of whole blood aggregometry and flow cytometry. The functional role of nAChR was evaluated using specific antagonists in aggregometry. CHRNA7, CHRNA4 and CHRNB2 gene transcripts and the corresponding proteins could be identified in CBMK during all stages of differentiation. Platelets contain nAChRα7 and nAChRβ2 but not nAChRα4. Nicotine had no effect on TPO-induced differentiation of CBMK. There was no significant difference in all platelet parameters of the smokers compared to the nonsmokers. In line with this, cholinergic gene transcripts as well as the encoded proteins were equally expressed in both the study groups. Despite our observation of nAChR expression in megakaryopoiesis and platelets, we were not able to detect effects of nicotine in our ex vivo and in vivo models. Thus, the functional role of the nAChR in these cells remains open.
Gesehen am 18.02.2019
Published online: 22 Apr 2015